Colored high-strength PET fiber and preparation method thereof
By using a colored high-strength modifier with PDI or NDI structure in PET fibers for melt spinning, the problem that PET fibers are difficult to take into account both high dyeing fastness and high strength is solved, and efficient dyeing and strength improvement is achieved.
Patent Information
- Application Number
- CN202411968789.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Existing PET fibers are difficult to take into account both high dyeing fastness and high strength, and there are problems with the compatibility between fiber and dye, which affects the dyeing fastness.
The PET melt containing a color high-strength modifier is used for melt spinning. The modifier has a linear molecular chain, a PDI or NDI structure in the middle, and aromatic rings at both ends. The fiber strength and dye bonding fastness are enhanced through the drafting process.
The high dyeing fastness and high strength are achieved, and the interface interaction in the microfiber structure of the fiber is enhanced, and the combination of dye and fiber is more stable, which improves the overall performance of the fiber.
Smart Images

Figure CN119753883A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of synthetic fibers and relates to a colored high-strength PET fiber and a preparation method thereof. Background Art
[0002] High-strength fibers are lightweight and have excellent tensile strength and toughness. They can effectively enhance the strength of composite materials, making them more reliable when subjected to high pressure and impact. The wear resistance of high-strength fibers can extend the service life of products and reduce maintenance costs. They are widely used in various fields, such as aerospace, automobiles, sports equipment, protective equipment, and construction. At present, there are four commonly used methods for preparing high-strength fibers: (1) gel spinning and high-draw fiber making process, which is to wet-spin a high molecular weight polyethylene solution into gel-like fibers and then extract the fibers at a high draw ratio; (2) liquid crystal spinning, which is to use a liquid crystal solution of a rigid polymer to draw through a spinning head in a semi-dry and semi-wet state to produce highly oriented crystals of a rigid polymer; (3) by changing the molecular chain structure of para-aromatic polyamide fibers, dissolving them in an organic solvent and then spinning them in a semi-dry and semi-wet state; (4) by melt spinning semi-rigid polymers, the fibers are made ultra-high strength. This process is specifically used to process aromatic polyesters.
[0003] Colored fibers are widely used in anti-counterfeiting technology, safety warnings, and enhancing product aesthetics. At present, there are two main methods for coloring colored fibers: (1) conventional fiber coloring, which is a method for dyeing hydrophobic and highly crystalline PET fibers. The key is to accelerate the diffusion rate of the dye in the fiber; (2) pre-spinning solution coloring, which is a method of adding appropriate pigments or dyes during the chemical fiber production process to directly produce colored fibers. It is also called pre-spinning coloring. Unlike conventional dyeing mechanisms, this pre-spinning coloring method allows the colorant to be evenly dispersed in the polymer. After spinning, the colorant is fixed in the fiber, and the coloring process is a physical change.
[0004] PET fiber has the advantages of good fiber-forming properties, high strength, wear resistance, and aging resistance. It has been widely used in the manufacture of various textiles. PET fiber that is both colored and high-strength has more important application value.
[0005] At present, there are few studies on PET fibers that are both colored and high-strength. The main method is to add masterbatch on the basis of producing high-strength fibers or spray color on them later to achieve color. The disadvantages of this method are: the added masterbatch will affect the fiber strength, or because high-strength fibers usually have a special chemical structure, it may lead to poor compatibility between the fiber and commonly used dyes, thereby affecting the color fastness. For example, patent application CN109322006A discloses a colored high-strength polyethylene fiber, and its preparation method includes the following steps: preparation of spinning solution; preparation of high-strength polyethylene fibers; spray modification of high-strength polyethylene fibers; ultraviolet light treatment. The process of achieving color and high strength in this preparation method is to spray color on the basis of producing high-strength fibers. The high-strength effect and the colored effect of the fiber are achieved separately. There is a compatibility problem between the fiber and the dye, which affects the color fastness.
[0006] Therefore, since the existing PET fibers cannot achieve both high color fastness and high strength, it is necessary to develop a PET fiber and a preparation method thereof that can achieve both high color fastness and high strength, so as to promote the further development of the PET industry. Summary of the invention
[0007] The purpose of the present invention is to solve the above problems existing in the prior art and to provide a colored high-strength PET fiber and a preparation method thereof.
[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing colored high-strength PET fiber comprises the steps of melt spinning a PET melt containing a colored high-strength modifier to obtain the colored high-strength PET fiber, wherein the colored high-strength modifier has a linear molecular chain, with PDI (3,4,9,10-perylene diimide, CAS No. 81-33-4) or NDI (1,4,5,8-naphthalene diimide, CAS No. 5690-24-4) in the middle and aromatic rings at both ends, and the melt spinning comprises a drawing process.
[0010] The principle of the invention is that during the drawing process, since the perylene ring or naphthalene ring of the PDI or NDI structure of the colored high-strength modifier has a conjugated rigid structure, and the aromatic rings (such as benzene ring, naphthalene ring, anthracene ring) connected at both ends of the PDI or NDI structure have a conjugated structure, under the action of the stress field, PDI and NDI are arranged along the orientation direction of the PET molecular chain, a large number of aromatic rings at both ends of the PDI or NDI structure can form a stable π-π interaction with the benzene ring on the PET fiber, and the interaction between the molecular chains is strengthened in the microfiber structure of the fiber. At the same time, the aromatic ring participates in the crystallization of the microfiber crystallization area, so the colored high-strength modifier enhances the interaction between the interfaces in the microfiber structure of the fiber, which is beneficial to improving the fiber strength and the bonding strength between the fiber and the colored high-strength modifier; in addition, PDI and NDI themselves have bright colors and can be used as the color source of the colored fiber.
[0011] As the preferred technical solution:
[0012] A method for preparing a colored high-strength PET fiber as described above, wherein the colored high-strength modifier is
[0013] Among them, n≥2.
[0014] In the method for preparing colored high-strength PET fiber as described above, the content of the colored high-strength modifier in the PET melt containing the colored high-strength modifier is 5-7wt%.
[0015] In the method for preparing a colored high-strength PET fiber as described above, the drafting multiple is 5-6 times, and four pairs of drafting rollers are used for drafting; the temperature of the first pair of drafting rollers is 140-150°C, and the spinning speed is 400-500m / min; the temperature of the second pair of drafting rollers is 239-250°C, and the spinning speed is 1255-1600m / min; the temperature of the third pair of drafting rollers is 246-250°C, and the spinning speed is 2000-2500m / min; the temperature of the fourth pair of drafting rollers is 245-250°C, and the spinning speed is 2400-2500m / min.
[0016] As described above, the preparation method of a colored high-strength PET fiber, the preparation process of the PET melt containing a colored high-strength modifier is: firstly, the colored high-strength modifier is melt-blended with PET chips to obtain a masterbatch with a colored high-strength modifier concentration of 40-45wt%, and then the masterbatch is melt-blended with the PET chips.
[0017] In the method for preparing a colored high-strength PET fiber as described above, a twin-screw extruder is used to melt-blend the masterbatch and the PET chips, and the temperatures of the zones of the twin-screw extruder are: zone one temperature 271-277°C, zone two temperature 289-293°C, zone three temperature 286-293°C, zone four temperature 289-295°C, and zone five temperature 292-295°C.
[0018] In the method for preparing colored high-strength PET fiber as described above, the process flow of melt spinning is: spinning→cooling→stretching→setting→winding.
[0019] In the method for preparing colored high-strength PET fiber as described above, the spinning temperature is 303-305°C; the wind temperature during cooling is 22-25°C, the wind relative humidity is 73-75%, and the wind speed is 0.7-0.8m / s; the shaping temperature is 88-109°C; and the winding speed is 4185-4200m / min.
[0020] The present invention also provides a colored high-strength PET fiber, which is prepared by the method for preparing a colored high-strength PET fiber as described in any one of the above items.
[0021] As the preferred technical solution:
[0022] The colored high-strength PET fiber as described above has a linear density deviation rate of 1-1.6%, a linear density variation coefficient of 0.5-2%, a linear density of 8500-9000 dtex, an elongation at break of 14.9-15.2%, a coefficient of variation of elongation at break of 4.5-5%, a coefficient of variation of breaking strength of 2.1-2.5%, a color fastness to light of level 8, a color fastness to soaping of level 5, a color fastness to water of level 5, a color fastness to rubbing of level 5, and a color fastness to perspiration of level 5.
[0023] Beneficial effects:
[0024] (1) The preparation method of the present invention strengthens the interaction between molecular chains in the microfiber structure of the fiber by adding PDI or NDI with aromatic rings (such as benzene ring, naphthalene ring, anthracene ring) at both ends as a colored high-strength modifier. At the same time, these aromatic rings participate in the crystallization of the microfiber crystalline region, thereby enhancing the interaction between the interfaces in the fiber microfiber structure, which is beneficial to improving the fiber strength and the bonding strength between the fiber and the colored high-strength modifier. In addition, the colored high-strength modifier itself has a bright color. As the color source of the colored fiber, it achieves both high fiber strength and high color fastness.
[0025] (2) The preparation method of the present invention adds a single colored high-strength modifier, the dispersion of the reaction system is uniform, complex additives and cumbersome process flow are avoided, and the preparation efficiency is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the structure of the colored high-strength PET fiber of Examples 1-4 of the present invention;
[0027] Figure 2 It is the colored high-strength modifier of Example 1 of the present invention 1 HNMR spectrum;
[0028] Figure 3 It is the colored high-strength modifier of Example 2 of the present invention 1 HNMR spectrum;
[0029] Figure 4 It is the colored high-strength modifier of Example 3 of the present invention 1 HNMR spectrum;
[0030] Figure 5 It is the colored high-strength modifier of Example 4 of the present invention 1 HNMR spectrum. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the claims of the application equally.
[0032] The following are the test methods for the relevant performance indicators in each embodiment and comparative example:
[0033] (1) Linear density deviation rate: tested in accordance with national standard GB / T4743-2009.
[0034] (2) Linear density variation coefficient: tested in accordance with method B of national standard GB / T14343-2003.
[0035] (3) Linear density: Tested in accordance with national standard GB / T16604-2017.
[0036] (4) Elongation at break: tested in accordance with national standard GB / T 3923.1-2013.
[0037] (5) Coefficient of variation of elongation at break: tested in accordance with national standard GB / T 3923.1-2013.
[0038] (6) Coefficient of variation of breaking strength: tested in accordance with national standard GB / T14344-2008.
[0039] (7) Color fastness to light: tested in accordance with national standard GB / T8427-2008.
[0040] (8) Color fastness to soap washing: tested in accordance with national standard GB / T3921-2008.
[0041] (9) Water fastness: tested in accordance with national standard GB / T5713-2013.
[0042] (10) Color fastness to rubbing: tested in accordance with national standard GB / T3920-2008.
[0043] (11) Color fastness to perspiration: tested in accordance with the national standard GB / T3922-2013.
[0044] Example 1
[0045] A method for preparing colored high-strength PET fiber, the specific steps are as follows:
[0046] (1) Raw material preparation;
[0047] PTCDA (3,4,9,10-perylenetetracarboxylic dianhydride): the structure is shown in formula (Ⅰ);
[0048]
[0049] Long-chain aniline: The structure is shown in formula (II), where n = 2;
[0050]
[0051] Imidazole;
[0052] N2;
[0053] Deionized water;
[0054] Anhydrous ethanol;
[0055] PET chips: fiber-grade semi-dull PET chips, manufactured by Yizheng Chemical Fiber, brand TFW100;
[0056] (2) Synthetic colored high-strength modifier
[0057] 5.1mmol PTCDA, 10.2mmol long-chain aniline and 88.1mmol imidazole were added to a three-necked flask in sequence, and the reaction was carried out at 140°C for 2h under N2 protection. After the reaction was completed, the reaction was cooled to 25°C, and deionized water was added to the three-necked flask. The imidazole was stirred and dispersed, and then filtered with a separatory funnel. The filter cake was rinsed with deionized water and anhydrous ethanol for 3 times in sequence, and a red powder product was obtained after drying, which was a colored high-strength modifier. The colored high-strength modifier was a PDI powder with a benzene ring. According to the national standard GB / T15000.3-2001, the purity was 86%, and the nuclear magnetic resonance hydrogen spectrum was as follows: Figure 2 As shown, δ = 4.05-4.25 is the chemical shift of H at CH2 connected to N, δ = 8.58-8.72 is the chemical shift of H on the perylene ring, and δ = 7.1-7.3 is the chemical shift of H on the side chain benzene ring;
[0058] The reaction of PTCDA and long-chain aniline is shown in formula (III);
[0059]
[0060] (3) preparing masterbatch;
[0061] The colored high-strength modifier and PET chips are melt-blended to prepare a masterbatch with a concentration of 45 wt %;
[0062] (4) melt spinning;
[0063] (4.1) Spinning: first, the masterbatch and the PET chips are melt-blended by a twin-screw extruder to obtain a PET melt, wherein the content of the colored high-strength modifier in the PET melt is 7 wt %. The temperatures of the zones of the twin-screw extruder are: zone 1 temperature 275° C., zone 2 temperature 290° C., zone 3 temperature 286° C., zone 4 temperature 289° C., zone 5 temperature 294° C., and then electrospinning is performed at a spinning temperature of 304° C.;
[0064] (4.2) Cooling: The wind temperature during cooling is 23°C, the wind relative humidity is 75%, and the wind speed is 0.7 m / s;
[0065] (4.3) Drafting: The drafting multiple is 6 times, and four pairs of drafting rollers are used for drafting; the temperature of the first pair of drafting rollers is 145°C, and the spinning speed is 400 m / min; the temperature of the second pair of drafting rollers is 246°C, and the spinning speed is 1600 m / min; the temperature of the third pair of drafting rollers is 250°C, and the spinning speed is 2000 m / min; the temperature of the fourth pair of drafting rollers is 250°C, and the spinning speed is 2400 m / min;
[0066] (4.4) Setting: The setting temperature is 109°C;
[0067] (4.5) Winding: The winding speed is 4190 m / min to obtain colored high-strength PET fiber.
[0068] The linear density deviation rate of the finally prepared colored high-strength PET fiber is 1.5%, the linear density variation coefficient is 0.6%, the linear density is 8900dtex, the elongation at break is 15%, the coefficient of variation of the elongation at break is 4.5%, the coefficient of variation of the breaking strength is 2.3%, the color fastness to light is level 8, the color fastness to soaping is level 5, the color fastness to water is level 5, the color fastness to rubbing is level 5, and the color fastness to sweat is level 5.
[0069] Comparative Example 1
[0070] A method for preparing PET fiber is basically the same as that in Example 1, except that PTCDA and long-chain aniline are used to replace the colored high-strength modifier, and the amounts of PTCDA and long-chain aniline used are the same as those in Example 1.
[0071] The linear density deviation rate of the finally prepared PET fiber is 4%, the linear density variation coefficient is 8%, the elongation at break is 10%, the variation coefficient of the elongation at break is 9%, the variation coefficient of the breaking strength is 7%, the color fastness to light is level 4, the color fastness to soaping is level 1, the color fastness to water is level 2, the color fastness to rubbing is level 1, and the color fastness to perspiration is level 2.
[0072] Example 2
[0073] A method for preparing colored high-strength PET fiber, the specific steps are as follows:
[0074] (1) Raw material preparation;
[0075] PTCDA: The structure is shown in formula (Ⅰ);
[0076] Long-chain naphthylamine: The structure is shown in formula (IV), where n = 3;
[0077]
[0078] Imidazole;
[0079] N2;
[0080] Deionized water;
[0081] Anhydrous ethanol;
[0082] PET chips: fiber-grade semi-dull PET chips, manufactured by Yizheng Chemical Fiber, brand TFW100;
[0083] (2) Synthetic colored high-strength modifier;
[0084] 5.1mmol PTCDA, 10.2mmol long-chain naphthylamine and 88.1mmol imidazole were added to a three-necked flask in sequence, and the reaction was carried out at 140°C for 2h under N2 protection. After the reaction was completed, the mixture was cooled to room temperature, deionized water was added, and the imidazole was stirred and dispersed, and then filtered with a separatory funnel. The filter cake was rinsed with deionized water and anhydrous ethanol for 3 times in sequence, and a red powder product was obtained after drying, which was a colored high-strength modifier. The colored high-strength modifier was a PDI powder with a naphthalene ring. According to the national standard GB / T 15000.3-2001, the purity was 82%, and the nuclear magnetic resonance hydrogen spectrum was as follows: Figure 3 As shown, δ = 4.05-4.25 is the chemical shift of H at CH2 connected to N, δ = 8.53-8.68 is the chemical shift of H on the perylene ring, and δ = 7.2-7.9 is the chemical shift of H on the side chain naphthalene ring;
[0085] The reaction of PTCDA and long-chain naphthylamine is shown in formula (V);
[0086]
[0087] (3) preparing masterbatch;
[0088] The colored high-strength modifier and PET chips are melt-blended to prepare a masterbatch with a concentration of 43 wt %;
[0089] (4) melt spinning;
[0090] (4.1) Spinning: The masterbatch and PET chips are first melt-blended by a twin-screw extruder to obtain a PET melt, wherein the content of the colored high-strength modifier in the PET melt is 6 wt %. The temperatures of the zones of the twin-screw extruder are: zone 1 temperature 277° C., zone 2 temperature 293° C., zone 3 temperature 289° C., zone 4 temperature 295° C., zone 5 temperature 295° C., and then electrospinning is performed at a spinning temperature of 305° C.;
[0091] (4.2) Cooling: The wind temperature during cooling is 22°C, the wind relative humidity is 74%, and the wind speed is 0.8 m / s;
[0092] (4.3) Drafting: The drafting multiple is 6 times, and four pairs of drafting rollers are used for drafting; the temperature of the first pair of drafting rollers is 140°C, and the spinning speed is 400 m / min; the temperature of the second pair of drafting rollers is 250°C, and the spinning speed is 1600 m / min; the temperature of the third pair of drafting rollers is 246°C, and the spinning speed is 2000 m / min; the temperature of the fourth pair of drafting rollers is 245°C, and the spinning speed is 2400 m / min;
[0093] (4.4) Setting: The setting temperature is 99°C;
[0094] (4.5) Winding: The winding speed is 4200 m / min to obtain colored high-strength PET fiber.
[0095] The linear density deviation rate of the finally prepared colored high-strength PET fiber is 1%, the linear density variation coefficient is 0.5%, the linear density is 8700dtex, the elongation at break is 15.2%, the coefficient of variation of the elongation at break is 4.6%, the coefficient of variation of the breaking strength is 2.2%, the color fastness to light is level 8, the color fastness to soaping is level 5, the color fastness to water is level 5, the color fastness to rubbing is level 5, and the color fastness to sweat is level 5.
[0096] Comparative Example 2
[0097] A method for preparing PET fiber is basically the same as Example 2, except that PTCDA and long-chain naphthylamine are used to replace the colored high-strength modifier, and the amounts of PTCDA and long-chain naphthylamine used are the same as those in Example 2.
[0098] The linear density deviation rate of the finally prepared PET fiber is 4.1%, the linear density variation coefficient is 8%, the elongation at break is 10%, the variation coefficient of the elongation at break is 8.9%, the variation coefficient of the breaking strength is 7%, the color fastness to light is level 4, the color fastness to soaping is level 1, the color fastness to water is level 2, the color fastness to rubbing is level 1, and the color fastness to perspiration is level 2.
[0099] Example 3
[0100] A method for preparing colored high-strength PET fiber, the specific steps are as follows:
[0101] (1) Raw material preparation;
[0102] PTCDA: The structure is shown in formula (Ⅰ);
[0103] Long-chain anthraceneamine: The structure is shown in formula (VI), wherein n=4;
[0104]
[0105] Imidazole;
[0106] N2;
[0107] Deionized water;
[0108] Anhydrous ethanol;
[0109] PET chips: fiber-grade semi-dull PET chips, manufactured by Yizheng Chemical Fiber, brand TFW100;
[0110] (2) Synthetic colored high-strength modifier;
[0111] 5.1mmol PTCDA, 10.2mmol long-chain anthracene amine and 88.1mmol imidazole were added to a three-necked flask in sequence, and the reaction was carried out at 140°C for 2h under N2 protection. After the reaction was completed, the mixture was cooled to room temperature, deionized water was added, and the imidazole was stirred and dispersed, and then filtered with a separatory funnel. The filter cake was rinsed with deionized water and anhydrous ethanol for 3 times in sequence, and a red powder product was obtained after drying, which was a colored high-strength modifier. The colored high-strength modifier was a PDI powder with an anthracene ring. According to the national standard GB / T 15000.3-2001, the purity was 82%, and the nuclear magnetic resonance hydrogen spectrum was as follows: Figure 4 As shown, δ = 4.05-4.23 is the chemical shift of H at CH2 connected to N, δ = 8.5-8.67 is the chemical shift of H on the perylene ring, and δ = 7.3-8.5 is the chemical shift of H on the side chain anthracene ring;
[0112] The reaction of PTCDA and long-chain anthracenamine is shown in formula (VII);
[0113]
[0114] (3) preparing masterbatch;
[0115] The colored high-strength modifier and PET chips were melt-blended to prepare a masterbatch with a concentration of 41 wt%;
[0116] (4) melt spinning;
[0117] (4.1) Spinning: first, the masterbatch and the PET chips are melt-blended by a twin-screw extruder to obtain a PET melt, wherein the content of the colored high-strength modifier in the PET melt is 5 wt %. The temperatures of the zones of the twin-screw extruder are: zone 1 temperature 273° C., zone 2 temperature 289° C., zone 3 temperature 293° C., zone 4 temperature 294° C., zone 5 temperature 293° C., and then electrospinning is performed at a spinning temperature of 303° C.;
[0118] (4.2) Cooling: The wind temperature during cooling is 25°C, the wind relative humidity is 73%, and the wind speed is 0.8 m / s;
[0119] (4.3) Drafting: The drafting multiple is 5 times, and four pairs of drafting rollers are used for drafting; the temperature of the first pair of drafting rollers is 148°C, and the spinning speed is 500 m / min; the temperature of the second pair of drafting rollers is 243°C, and the spinning speed is 1255 m / min; the temperature of the third pair of drafting rollers is 247°C, and the spinning speed is 2500 m / min; the temperature of the fourth pair of drafting rollers is 246°C, and the spinning speed is 2500 m / min;
[0120] (4.4) Setting: The setting temperature is 102°C;
[0121] (4.5) Winding: The winding speed is 4185 m / min to obtain colored high-strength PET fiber.
[0122] The linear density deviation rate of the finally prepared colored high-strength PET fiber is 1.2%, the linear density variation coefficient is 2%, the linear density is 9000dtex, the elongation at break is 14.9%, the coefficient of variation of the elongation at break is 4.7%, the coefficient of variation of the breaking strength is 2.1%, the color fastness to light is level 8, the color fastness to soaping is level 5, the color fastness to water is level 5, the color fastness to rubbing is level 5, and the color fastness to sweat is level 5.
[0123] Comparative Example 3
[0124] A method for preparing PET fiber is basically the same as Example 3, except that PTCDA and long-chain anthracenamine are used to replace the colored high-strength modifier, and the amounts of PTCDA and long-chain anthracenamine used are the same as those in Example 3.
[0125] The linear density deviation rate of the finally prepared PET fiber is 4.1%, the linear density variation coefficient is 8%, the elongation at break is 10%, the variation coefficient of the elongation at break is 8.7%, the variation coefficient of the breaking strength is 7%, the color fastness to light is level 4, the color fastness to soaping is level 1, the color fastness to water is level 2, the color fastness to rubbing is level 1, and the color fastness to perspiration is level 2.
[0126] Example 4
[0127] A method for preparing colored high-strength PET fiber, the specific steps are as follows:
[0128] (1) Raw material preparation;
[0129] NTCDA (1,4,5,8-naphthalenetetracarboxylic anhydride): the structure is shown in formula (VIII);
[0130]
[0131] Long-chain aniline: The structure is shown in formula (II), where n = 5;
[0132] Imidazole:
[0133] N2;
[0134] Deionized water;
[0135] Anhydrous ethanol;
[0136] PET chips: fiber-grade semi-dull PET chips, manufactured by Yizheng Chemical Fiber, brand TFW100;
[0137] (2) Synthetic colored high-strength modifier;
[0138] 7.5mmol NTCDA, 10.2mmol long-chain aniline and 88.1mmol imidazole were added to a three-necked flask in sequence, and the reaction was carried out at 140°C for 2h under N2 protection. After the reaction was completed, the mixture was cooled to room temperature, and deionized water was added to the three-necked flask. The imidazole was stirred and dispersed, and then filtered with a separatory funnel. The filter cake was rinsed with deionized water and anhydrous ethanol for 3 times in sequence, and dried to obtain a yellow powder product, which was a colored high-strength modifier. The colored high-strength modifier was an NDI powder with a benzene ring. According to the national standard GB / T 15000.3-2001, the purity was 81%, and the nuclear magnetic resonance hydrogen spectrum was as follows: Figure 5 As shown, δ = 4.35-4.4 is the chemical shift of H at CH2 connected to N, δ = 8.75-8.8 is the chemical shift of H on the naphthalene ring, and δ = 7.1-7.3 is the chemical shift of H on the side chain benzene ring;
[0139] The reaction of NTCDA and long-chain aniline is shown in formula (IX);
[0140]
[0141] (3) preparing masterbatch;
[0142] The colored high-strength modifier and PET chips are melt-blended to prepare a masterbatch with a concentration of 40wt%;
[0143] (4) melt spinning;
[0144] (4.1) Spinning: first, the masterbatch and the PET chips are melt-blended by a twin-screw extruder to obtain a PET melt, wherein the content of the colored high-strength modifier in the PET melt is 5 wt %. The temperatures of the zones of the twin-screw extruder are: zone 1 temperature 271° C., zone 2 temperature 292° C., zone 3 temperature 292° C., zone 4 temperature 294° C., zone 5 temperature 292° C., and then electrospinning is performed at a spinning temperature of 304° C.;
[0145] (4.2) Cooling: The wind temperature during cooling is 25°C, the wind relative humidity is 74%, and the wind speed is 0.7 m / s;
[0146] (4.3) Drafting: The drafting multiple is 6 times, and four pairs of drafting rollers are used for drafting; the temperature of the first pair of drafting rollers is 150°C, and the spinning speed is 400 m / min; the temperature of the second pair of drafting rollers is 239°C, and the spinning speed is 1600 m / min; the temperature of the third pair of drafting rollers is 250°C, and the spinning speed is 2000 m / min; the temperature of the fourth pair of drafting rollers is 248°C, and the spinning speed is 2400 m / min;
[0147] (4.4) Setting: The setting temperature is 88°C;
[0148] (4.5) Winding: The winding speed is 4189 m / min, and the colored high-strength PET fiber is obtained.
[0149] The linear density deviation rate of the finally prepared colored high-strength PET fiber is 1.6%, the linear density variation coefficient is 1.3%, the linear density is 8500dtex, the elongation at break is 15.1%, the coefficient of variation of the elongation at break is 5%, the coefficient of variation of the breaking strength is 2.5%, the color fastness to light is level 8, the color fastness to soaping is level 5, the color fastness to water is level 5, the color fastness to rubbing is level 5, and the color fastness to sweat is level 5.
[0150] Comparative Example 4
[0151] A method for preparing PET fiber is basically the same as that in Example 4, except that NTCDA and long-chain aniline are used to replace the colored high-strength modifier, and the amounts of NTCDA and long-chain aniline used are the same as those in Example 4.
[0152] The linear density deviation rate of the finally prepared PET fiber is 4.1%, the linear density variation coefficient is 8%, the elongation at break is 10%, the variation coefficient of the elongation at break is 8.6%, the variation coefficient of the breaking strength is 7%, the color fastness to light is level 3, the color fastness to soaping is level 1, the color fastness to water is level 2, the color fastness to rubbing is level 1, and the color fastness to perspiration is level 2.
[0153] In summary, by comparing Examples 1-4 with Comparative Examples 1-4, the linear density deviation rate, linear density variation coefficient, elongation at break variation coefficient, and breaking strength variation coefficient of the PET fibers finally prepared in Examples 1-4 are significantly lower than those of the PET fibers finally prepared in Comparative Examples 1-4, and the color fastness to light, color fastness to soaping, color fastness to water, color fastness to rubbing, and color fastness to perspiration of the PET fibers finally prepared in Examples 1-4 are significantly higher than those of the PET fibers finally prepared in Comparative Examples 1-4. This is because Examples 1-4 have a better linear density than the fibers prepared in Comparative Examples 1-4. During the fiber drawing process, the perylene ring or naphthalene ring of the PDI or NDI structure of the above-mentioned colored high-strength modifier has a conjugated rigid structure, and the aromatic rings (such as benzene, naphthalene, anthracene) connected at both ends of PDI or NDI also have a conjugated structure. Under the action of the stress field, PDI is arranged along the orientation direction of the PET molecular chain. These aromatic rings can form a stable π-π interaction with the benzene ring on the PET fiber, which strengthens the interaction between molecular chains in the fiber microfiber structure and increases the strength of the fiber; at the same time, these aromatic rings participate in the crystallization of the microfiber crystallization area (such as Figure 1 As shown), the colored high-strength modifier is used to enhance the interaction between interfaces in the fiber microfiber structure, which is beneficial to improving the fiber strength. The strong interaction between the dye and the fiber also imparts high color fastness.
Claims
1. A method for preparing colored high-strength PET fiber, characterized in that: The colored high-strength PET fiber is obtained by melt spinning the PET melt containing the colored high-strength modifier, wherein the colored high-strength modifier has a linear molecular chain, with PDI or NDI in the middle and aromatic rings at both ends, and the melt spinning includes a drawing process.
2. The method for preparing a colored high-strength PET fiber according to claim 1, characterized in that: Colored high strength modifier is Among them, n≥2.
3. The method for preparing a colored high-strength PET fiber according to claim 1, characterized in that: In the PET melt containing the colored high-strength modifier, the content of the colored high-strength modifier is 5-7wt%.
4. The method for preparing a colored high-strength PET fiber according to claim 1, characterized in that: The stretching multiple is 5-6 times, and four pairs of stretching rollers are used for stretching; the temperature of the first pair of stretching rollers is 140-150℃, and the spinning speed is 400-500m / min; the temperature of the second pair of stretching rollers is 239-250℃, and the spinning speed is 1255-1600m / min; the temperature of the third pair of stretching rollers is 246-250℃, and the spinning speed is 2000-2500m / min; the temperature of the fourth pair of stretching rollers is 245-250℃, and the spinning speed is 2400-2500m / min.
5. The method for preparing a colored high-strength PET fiber according to claim 1, characterized in that: The preparation process of the PET melt containing a colored high-strength modifier is as follows: firstly, the colored high-strength modifier is melt-blended with PET chips to obtain a master batch with a colored high-strength modifier concentration of 40-45wt%, and then the master batch is melt-blended with the PET chips.
6. The method for preparing a colored high-strength PET fiber according to claim 5, characterized in that: The masterbatch and PET chips are melt-blended using a twin-screw extruder, and the temperatures of each zone of the twin-screw extruder are: zone 1 temperature 271-277°C, zone 2 temperature 289-293°C, zone 3 temperature 286-293°C, zone 4 temperature 289-295°C, zone 5 temperature 292-295°C.
7. The method for preparing a colored high-strength PET fiber according to claim 1, characterized in that: The process flow of melt spinning is: spinning → cooling → drawing → shaping → winding.
8. The method for preparing a colored high-strength PET fiber according to claim 7, characterized in that: The spinning temperature is 303-305°C; the wind temperature during cooling is 22-25°C, the wind relative humidity is 73-75%, and the wind speed is 0.7-0.8m / s; the shaping temperature is 88-109°C; and the winding speed is 4185-4200m / min.
9. A colored high-strength PET fiber, characterized in that: The colored high-strength PET fiber is prepared by the preparation method of any one of claims 1 to 8.
10. The colored high-strength PET fiber according to claim 9, characterized in that: The linear density deviation rate of colored high-strength PET fiber is 1-1.6%, the linear density variation coefficient is 0.5-2%, the linear density is 8500-9000dtex, the elongation at break is 14.9-15.2%, the elongation at break variation coefficient is 4.5-5%, the breaking strength variation coefficient is 2.1-2.5%, the color fastness to light is level 8, the color fastness to soaping is level 5, the color fastness to water is level 5, the color fastness to friction is level 5, and the color fastness to sweat is level 5.
Citation Information
Patent Citations
Colored high-strength polyethylene fibers and preparation method thereof
CN109322006A
Polymer-based fluorescent functional composite material and fusing process method thereof
CN102690438A
Intelligent photochromic material as well as preparation method and application thereof
CN114516965A
Photochromic master batch as well as preparation method and application thereof
CN116694032A
N1n-dimethyldiimide perilene-3,4,9,10 of tetracarboxylic acid with improved coloristic and strength properties on polymeric materials and method of producing same
SU1321731A1